2014
DOI: 10.1021/cs501511x
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium-Catalyzed Dehydration and Deoxydehydration of Alcohols and Polyols: Opportunities for the Formation of Olefins from Biomass

Abstract: In view of the depletion of petroleum oils, new synthetic routes for the sustainable production of chemicals, fuels, and energy from renewable biomass sources are currently widely investigated. In particular, nonedible sugars and polyols are promising starting materials to produce olefins by dehydration, deoxygenation, or deoxydehydration (DODH) of these poly vicinal alcohols. In this perspective, we highlight the recent evolution of rhenium-catalyzed dehydration and DODH of biomass-derived alcohols and polyol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
120
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 96 publications
3
120
0
Order By: Relevance
“…The in situ generated catalyst with monodentate P n Oct 3 and Ru(acac) 3 in the presence of NH 4 PF 6 gave GVL in 99% yield at 160 o C and 100 bar H 2 in neat LA. Applying the same reaction conditions using the bidentate DPPB and tridentate ligand triphos ligands gave yields of 89% and 8% of GVL respectively.…”
Section: Hydrogenation Of Levulinic Acid (La) To γ-Valerolactone (Gvl)mentioning
confidence: 99%
See 4 more Smart Citations
“…The in situ generated catalyst with monodentate P n Oct 3 and Ru(acac) 3 in the presence of NH 4 PF 6 gave GVL in 99% yield at 160 o C and 100 bar H 2 in neat LA. Applying the same reaction conditions using the bidentate DPPB and tridentate ligand triphos ligands gave yields of 89% and 8% of GVL respectively.…”
Section: Hydrogenation Of Levulinic Acid (La) To γ-Valerolactone (Gvl)mentioning
confidence: 99%
“…[28][29][30][31] In early pioneering studies Osakada et al, [32] showed the activation of C-O bonds of five membered cyclic anhydride, aldehydic and keto acids using two different ruthenium ( [10] demonstrated the use of an in situ generated Ru catalyst using a combination of Ru(acac) 3 and the strongly electron donating phosphine P n Bu 3 in the presence of NH 4 PF 6 for LA hydrogenation to GVL ( [33] reported the effect of the mondentate and chelating phosphines: trioctylphosphine (P n Oct 3 ), 1,4-diphenylphosphinobutane (DPPB) and triphos ( fig. 2) and various acidic additives for the transformation of LA.…”
Section: Hydrogenation Of Levulinic Acid (La) To γ-Valerolactone (Gvl)mentioning
confidence: 99%
See 3 more Smart Citations